Effects of wall masonry layer's thermophysical properties and insulation position on time lag and decrement factor. Issue 2 (April 2016) - Zhang, Lianying; Zhang, Jiyuan; Wang, Fenghao; Wang, Yuan
In this study, effects of the thermophysical properties of the wall masonry layer on the time lag and decrement factor of the composite wall were investigated numerically. For this purpose, the time lag and the decrement factor of six kinds of composite walls were calculated using the software FLUENT. The results show that the time lag would increase with an increase in the heat capacity of the masonry wall layer and would decrease with an increase in the thermal conductivity of the masonry wall; the decrement factor would decrease with an increase in the heat capacity of the masonry wall layer, but would increase with an increase in the thermal conductivity of the masonry wall. In the walls with one insulation layer, the wall with insulation on the outer surface would always have the smallest decrement factor. In the walls with two insulation layers, the wall with the insulation partly in the middle and partly on the outer surface would always have the highest time lag and the wall with the insulation partly on the inner surface and partly on the outer surface would always have the smallest decrement factor.